Identifying the challenges of implementing the use of statistical thinking principles and concepts for dental services organizations in the Kingdom of Saudi Arabia: A mixed survey and observational study - Abdulrahman Ahmed Alshehri (Wolters Kluwer Medknow Publications, 2024)
Introduction: Identifying obstacles that prevent the adoption and implementation of statistical techniques (STes) could enlighten policymakers' decisions and pave the way for fostering the attainment of predetermined targets in the health-care sector, in line with Saudi Vision 2030 and the transformational period in the health-care sector, including dental services. Aims: The study aimed to identify and discuss the challenges preventing the adoption of statistical thinking (STk) and statistical techniques in dental service organizations in Saudi Arabia. Materials and Methods: The study applied a mixed design to investigate the researched case. An exploratory approach was used to obtain an initial understanding of the case, explore it, and find factual evidence of its structure, dynamics, and context. On the other hand, an explanatory approach was employed to address inquiries of the mechanisms and rationales behind a specific event. This study employs a triangulation concept, combining survey results and a comprehensive examination of charts, reports, and documentation to unravel the intricate operational performance and decision-making (DM) facets. Results and Discussion: The survey, conducted over two time points with 57 and 49 participants, revealed a positive trajectory in crucial elements, notably a two-fold improvement observed in the STk factor. The regression analysis validated these trends, revealing numerical shifts in several elements and robust model fitting. Documentation analysis, spanning 120 documents, 23 reports, and 13 interview papers, enriched our understanding of the organizational landscape. The initial identification of 208 codes was thematically refined, encapsulating diverse challenges ranging from workforce dynamics to data quality and facility management. The discussion encompasses findings on organizational efficacy, resource constraints, structural inflexibility, and challenges in managerial DM. It highlights systemic inefficiencies, unbalanced demand-support dynamics, and consequences on service quality and stakeholder satisfaction. Conclusion: The study explored the adoption of new healthcare management systems in Saudi Arabia, focusing on STk and STes integration, and highlights significant cultural advancements.